Pengaruh Pembelajaran Daring Menggunakan Model Problem-based Learning (PBL) Terhadap Hasil Belajar Siswa - Dwi Cahyani; Anandita Eka Setiadi; Mahwar Qurbaniah (BIO-EDU: Jurnal Pendidikan Biologi, 2022)
Most students consider the excretory system material to be difficult to understand so that students often only memorize it in their learning. Teachers generally use the Teacher Centered Learning (TCL) model in online learning. This study aims to determine the effect of online learning during the pandemic using the Problem-Based Learning (PBL) model on student learning outcomes. The research was conducted in class XI SMA Islamiyah Pontianak. The research method uses Quasi Experiment. The study used class XI IPS 2 as the experimental class and class XI IPS 1 as the control class which was selected using purposive sampling technique. Data was collected by means of learning outcomes tests before and after learning. The research data were analyzed using N-Gain. The results showed that in the experimental class the N-Gain score was 0.46 (medium category), while in the control class the N-Gain score was 0.19 (low category). Based on the results of the study, it was concluded that there was an effect of the PBL learning model on the learning outcomes of the XI grade students of SMA Islamiyah Pontianak.